Implementing oncology clinical trials in Nigeria: A model for Capacity building. (2020)
Background: There is both higher mortality and morbidity from cancer in low and medium income countries (LMICs) compared with high income countries (HICs). Clinical trial activities and development of more effective and less toxic therapies have led to signi¦ cant improvements in morbidity and mortality from cancer in HICs. Unfortunately, clinical trials remain low in LMICs due to poor infrastructure and paucity of experienced personnel to execute clinical trials. There is an urgent need to build local capacity for evidence based treatment for cancer patients in LMICs. Methods: We conducted a survey at facilities in four Teaching Hospitals in South West Nigeria using a checklist of information on various aspects of clinical trial activities. The gaps identi¦ ed were addressed using resources sourced in partnership with investigators at HIC institutions. Results: De¦ cits in infrastructure were in areas of patient care such as availability of oncology pharmacists, standard laboratories and diagnostic facilities, clinical equipment maintenance and regular calibrations, trained personnel for clinical trial activities, investigational products handling and disposals and lack of standard operating procedures for clinical activities. There were two GCP trained personnel, two study coordinators and one research pharmacist across the four sites. Interventions were instituted to address the observed de¦ cits in all four sites which are now well positioned to undertake clinical trials in oncology. Training on all aspects of clinical trial was also provided. Conclusions: Partnerships with institutions in HICs can successfully identify, address, and improve de¦ cits in infrastructure for clinical trial in LMICs. The HICs should lead in providing funds, mentorship and training for LMIC institutions to improve and expand clinical trials in LMIC countries.